How do childcare and pregnancy affect the academic success of college students?. Issue 2 (12th February 2023) - Manze, Meredith; Watnick, Dana; Freudenberg, Nicholas
Abstract: Objective: We examined socioeconomic, academic, and health-related factors associated with respondent reports that childcare interfered with academics. Participants: 176 undergraduate student parents Methods: We administered a cross-sectional survey to a representative sample of students at a public university in New York City. Using a sub-set of those who reported being parents/guardians (n = 176), we conducted bivariate analyses to assess factors associated with childcare problems interfering with school. Results: About 30% of the sample reported that childcare interfered with school somewhat/moderately/a lot in the last year. Compared to those with no/little perceived interference, they were significantly more likely to need mental health treatment (30% vs. 13%; p  < 0.01), worry that they would run out of food sometimes/often (32% vs. 16%; p  < 0.01), and experience housing problems (26% vs. 9%; p  < 0.01). Conclusions: Offering mental healthcare and services addressing food and housing insecurity can help college students to navigate challenges inherent to being a student parent.